Simulação de um alimentador Venturi em trecho ascendente no transporte pneumático de sólidos - Padua, Thiago Faggion de (2012)
The radial and axial distributions of coarse solids when fed directly in a riser are unknown, despite this type of feeding is very important for drying and preheating of solids during conveying. In this context, this thesis focused on studying the diluted conveying of coarse solids in a riser that was fed by a Venturi feeder in vertical orientation. Experiments were done with particles of 1mm averaged diameter conveyed in a riser (5.32cm of diameter) to obtain the mass loading ratio used in simulations. The assays also made pressure data available to verify the simulations. Eulerian simulations using models based on kinetic granular theory were done. The main goal was to evaluate solids distribution in gas-solid flow for this type of system. The 2D simulations were used to get a stable pattern downstream the feeder after the development length. However, the solid feeding structures generated near feeding percolated the entire riser and, as a consequence, there was no stable pattern. As a consequence, no pattern was found to represent solid phase behavior, since the axial symmetric assumption is invalid for the Venturi feeder. Therefore, only 3D simulations can be used to study asymmetric feeding for the conditions applied, even for a relatively long riser with small diameter. Experimental pressure data was approximately predicted by 3D simulations and prediction was better as the mesh was refined. However, the refined meshes applied in shorter risers to decrease computational effort showed the same solid flow behavior that was seen in the coarser mesh. The 3D simulations showed that there were clusters in the entire experimental riser. Moreover, clusters were generated by solid phase flow near feeding and some of them percolated the entire riser while mixing others. In addition, simulations showed that the bypass region on feeding is in the opposite side from feeding pipe.